A rhetorical analysis of selected speeches of Dr. Zakir Naik - Anis Izzati Bt Ismail (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Recent decades have witnessed the spread of the English language across the globe which has become the lingua franca of the 21st century. It has empowered and brought mobility to its users, especially non-native speakers of the English language. According to Al-Faruqi (1986), the English language has gained its status as language of various communicative functions around the world, especially among the Muslims. The English language has been used by Muslims as a medium of communication, commerce and education. Recently, the English language has also been used as a means to spread the message of Islam globally. Thus, it is important for those who propagate Islam to know and apply rhetorical strategies used by successful Muslim preachers. This study aims to analyze the rhetorical strategies by Dr. Zakir Naik. Qualitative data collection is employed. Three speeches of Dr. Zakir Naik are selected. They are first transcribed, categorized and analyzed. The findings indicate that Dr. Zakir Naik employ logical modes (logos) which are allusion, rhetorical question, fact, enthymeme, example and statistics to strengthen his arguments. He also employs repetition, parallelism and humor to stir the hearer's emotions (pathos) and persuade his audience. Findings also indicate that humor was utilized by Dr. Zakir Naik to lighten the mood, especially when discussing serious issues such as mass killing and terrorism. Dr. Zakir Naik's ethic (ethos) when he appears to be the man of knowledge when he provides evidence and a sound understanding of major religious scriptures and subject matters. In terms of linguistics, findings show that Dr. Zakir Naik employs Islamic English, repetition and parallelism to make his speech and argument more interesting to the listeners. Overall findings indicate that Islamic English is the main language strategy utilized by Dr. Zakir Naik. It is used by Dr. Zakir Naik to maintain Arabic terms in his speeches when there is an absence of equivalent English words. An attempt to translate would lead to distortion of meanings. It is also found that Islamic English is mainly used by Dr. Zakir Naik to correct misconceptions and spread the message of Islam, parallel to the objectives of da'wah. The findings of this rhetorical study provide essential theoretical and practical implications for future Muslim preachers to propagate Islam.